Influence of heavy metals on the occurrence of Antarctic soil microalgae. Issue 6 (December 2021) - Dang, Nguk-Ling; Chu, Wan-Loy; Yap, Kok-Seng Ivan; Kok, Yih-Yih; Phang, Siew-Moi; Chan, Kok-Keong; Convey, Peter
Abstract: Human- and animal-impacted sites in Antarctica can be contaminated with heavy metals, as well as areas influenced by underlying geology and naturally occurring minerals. The present study examined the relationship between heavy metal presence and soil microalgal occurrence across a range of human-impacted and undisturbed locations on Signy Island. Microalgae were identified based on cultures that developed after inoculation into an enriched medium. Twenty-nine microalgae representing Cyanobacteria, Bacillariophyta, Chlorophyta and Tribophyta were identified. High levels of As, Ca, Cd, Cu and Zn were detected in Gourlay Peninsula and North Point, both locations hosting dense penguin rookeries. Samples from Berntsen Point, the location of most intense human activity both today and historically, contained high levels of Pb. The contamination factor and pollution load index confirmed that the former locations were polluted by Cd, Cu and Zn, with these being of marine biogenic origin. Variation in the microalgal community was significantly correlated with concentrations of Mn, Ca, Mg, Fe, Zn, Cd, Co, Cr and Cu. However, the overall proportion of the total variation contributed by all metals was low (16.11%). Other factors not measured in this study are likely to underlie the majority of the observed variation in microalgal community composition between sampling locations.